Comorbidities in patients with chronic hepatitis C and hepatitis B on hemodialysis. Issue 8 (10th March 2021) - Hsu, Po‐Yao; Wei, Yu‐Ju; Liang, Po‐Cheng; Lee, Jia‐Jung; Niu, Sheng‐Wen; Huang, Jiun‐Chi; Hsu, Cheng‐Ting; Jang, Tyng‐Yuan; Huang, Ching‐I; Lin, Yi‐Hung; Hsieh, Ming‐Yen; Hsieh, Meng‐Hsuan; et al.
Abstract: Background and Aim: Hemodialysis patients are at increased risk of hepatitis B virus (HBV) and hepatitis C virus (HCV) infection. Both HBV and HCV infections lead to risks of end‐stage liver diseases and extrahepatic manifestations. This study aimed to investigate hepatic and extrahepatic comorbidities in hemodialysis patients with HBV or HCV infections compared with those without viral hepatitis. Methods: A total of 1910 hemodialysis patients, including 159 HCV viremic patients (HCV group), 217 seropositive for HBV surface antigen (HBsAg, HBV group) and 1534 seronegative for both anti‐HCV and HBsAg (non‐B and non‐C [NBNC] group), from 23 hemodialysis centers were enrolled. Comorbidities were classified into 10 categories by the International Classification of Diseases‐10th Revision. Results: Among the 1910 patients, the mean age was 64.6 years, and 52.7% were male patients. A total of 1834 (96%) patients had at least one comorbidity, and the mean number of comorbidities was 2.9 ± 1.5 per person. The three most common comorbidities were hypertension, diabetes, and ischemic heart diseases. The mean number of comorbidities per person was significantly higher in the HCV group (3.3 ± 1.7) than in the HBV (2.7 ± 1.5, P < 0.001) and NBNC groups (2.9 ± 1.5, P = 0.004), mainly due to the higher prevalence of ischemic heart disease, respiratory disorders, and mental/behavioral disorders. The HBV and NBNC groups exhibited comparable burdens of comorbidities. Conclusions: Hemodialysis patients had a high prevalence of multiple comorbidities. Hemodialysis patients with HCV exhibited a higher burden of comorbidities, especially ischemic heart diseases, respiratory disorders, and mental/behavioral disorders, than HBV and NBNC patients did.